Implementasi Pembelajaran Berdiferensiasi Terhadap Perkembangan Kognitif Peserta Didik di Kelas Inklusi PKBM Insan Cerdas Indonesia - Puspitasari, Yuni; I Ketut Atmaja Johny Artha; Susilo, Heryanto (Transformasi : Jurnal Penelitian dan Pengembangan Pendidikan Non Formal Informal, 2025)
Abstract: The purpose of this research is to describe how differentiated instruction is used in inclusive classes in non-formal educational settings, particularly at PKBM Insan Cerdas Indonesia. It was discovered that differentiated learning was used thoroughly, beginning with initial assessment, planning, execution, and learning evaluation, using a descriptive qualitative method with in-depth interviewing techniques, observation, and documentation. These results demonstrate how well the differentiation method works to meet the learning requirements of students with a range of backgrounds and abilities. According to the research findings, there are three primary steps involved in implementing differentiated learning: preliminary assessment, lesson planning, and classroom implementation. The lesson plan is developed based on the results of the initial assessment, which includes talent mapping tools, psychological assessments, and Multiple Intelligence Research (MIR). Teachers, psychologists, guidance counselors, and parents work together during the planning phase. In order to meet the various requirements of students, differentiated learning stresses changes to the learning environment, procedures, products, and material. Better logical thinking abilities, a stronger conceptual comprehension, and students’ confidence in voicing their thoughts and finishing projects are all results of using this method. Abstrak: Penelitian ini bertujuan untuk menggambarkan implementasi pembelajaran berdiferensiasi pada kelas inklusi di satuan pendidikan nonformal, khususnya di PKBM Insan Cerdas Indonesia. Melalui pendekatan kualitatif deskriptif dengan teknik wawancara mendalam, observasi, dan dokumentasi, ditemukan bahwa pembelajaran berdiferensiasi diimplementasikan secara menyeluruh mulai dari asesmen awal, perencanaan, pelaksanaan, hingga evaluasi pembelajaran. Temuan ini menunjukkan efektivitas pendekatan diferensiasi dalam mengakomodasi kebutuhan belajar peserta didik dengan latar belakang dan potensi yang beragam. Berdasarkan temuan penelitian, terdapat tiga langkah utama yang terlibat dalam penerapan pembelajaran terdiferensiasi: asesmen awal, perencanaan pembelajaran, dan implementasi di kelas. Rencana pembelajaran disusun berdasarkan hasil asesmen awal, yang mencakup alat pemetaan bakat, asesmen psikologis, dan Penelitian Kecerdasan Ganda (MIR). Guru, psikolog, konselor bimbingan, dan orang tua bekerja sama selama fase perencanaan. Untuk memenuhi berbagai kebutuhan siswa, pembelajaran terdiferensiasi menekankan perubahan pada lingkungan belajar, prosedur, produk, dan materi. Kemampuan berpikir logis yang lebih baik, pemahaman konseptual yang lebih kuat, dan kepercayaan diri siswa dalam menyuarakan pemikiran dan menyelesaikan proyek merupakan hasil dari penerapan metode ini.